Cutts family papers - Cutts, Anna Holyoke; Cutts, Charles, 1769-1846.; Cutts, James Madison; Cutts, James Madison, 1805-1863.; Cutts, Lucy Henry Southall; Cutts, Richard, 1771-1845.; Douglas, Stephen A. (Stephen Arnold), 1813-1861.; Madison, Dolley, 1768-1849.
Correspondence of members of the Cutts family, notes and copies of poems by Dolley Madison, writings of James Madison Cutts II, newspaper clippings, photographs, genealogical material, certificates, poems, and copies of poems by John Quincy Adams, Louisa Catherine Adams, and Henry Wadsworth Longfellow. Correspondence relates chiefly to family matters with reference to political and social affairs in 19th century U.S. Correspondents include James Buchanan, Henry Clay, John J. Crittenden, Edward Everett, Millard Fillmore, and William McKinley.
Cutts family members including Charles Cutts, U.S. senator from New Hampshire, his wife Lucy Henry Southall Cutts, his mother Anna Holyoke Cutts, and his cousin Richard Cutts, U.S. representative from Massachusetts; Richard's son James Madison Cutts I and grandson James Madison Cutts II (1837-1903); and Dolley Madison and Stephen Arnold Douglas, collateral members of the family.
Collection material in English.
Keywords: Adams, John Quincy, -- 1767-1848.; Adams, Louisa Catherine, -- 1775-1852.; Buchanan, James, -- 1791-1868 -- Correspondence; Clay, Henry, -- 1777-1852 -- Correspondence; Crittenden, John J. -- 1787-1863 -- Correspondence; Everett, Edward, -- 1794-1865 -- Correspondence; Fillmore, Millard, -- 1800-1874 -- Correspondence; Longfellow, Henry Wadsworth, -- 1807-1882; McKinley, William, -- 1843-1901 -- Correspondence; Cutts family -- Correspondence; United States -- Politics and government -- 19th century; United States -- Social life and customs -- 19th century